2004
DOI: 10.1038/sj.bjc.6601700
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of cisplatin analogue nedaplatin (254-S) and paclitaxel in patients with unresectable squamous cell carcinoma

Abstract: The recommended phase II dose of paclitaxel 180 mg m(-2) given as a 3-h infusion followed by nedaplatin 100 mg m(-2) in a 1-h infusion every 3-4 weeks was determined in 52 chemo-naive patients with unresectable squamous cell carcinoma (SCC), with a promising response rate for lung SCC of 55%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Naito [ 5 ] investigated efficacy of a nedaplatin and docetaxel regimen in advanced squamous cell lung carcinoma. The doublet produced an objective response rate of 62% and an overall survival of 16.1 months, which was comparable to the results in earlier studies [ 6 , 7 ]. But although attention has been paid to the efficacy of nedaplatin and its comparison to cisplatin, few studies have focused on its histological specificity.…”
Section: Introductionsupporting
confidence: 88%
“…Naito [ 5 ] investigated efficacy of a nedaplatin and docetaxel regimen in advanced squamous cell lung carcinoma. The doublet produced an objective response rate of 62% and an overall survival of 16.1 months, which was comparable to the results in earlier studies [ 6 , 7 ]. But although attention has been paid to the efficacy of nedaplatin and its comparison to cisplatin, few studies have focused on its histological specificity.…”
Section: Introductionsupporting
confidence: 88%
“…The antineoplastic activity of nedaplatin, a cisplatin derivate developed in 1983 [ 43 ], might be mediated by mechanisms distinct from those of p53-dependent early apoptosis [ 44 ]. Several studies have demonstrated that a nedaplatin-based treatment regimen [ 45 47 ] for squamous cell lung cancer is superior to a cisplatin or carboplatin-based regimen [ 48 ]. Our work provides a potential rationale for nedaplatin as the optimal choice for NSCLC patients with KEAP1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the phase I study of the combination of paclitaxel and nedaplatin for uterine cervical cancer has not been reported, Yoshiike et al reported the recommended dose of paclitaxel and nedaplatin were 180 mg/m 2 and 80 mg/m 2 , respectively which resulted from a phase I study for non-small cell lung cancer [12]. Sekine et al conducted a phase I study for un-resectable squamous cell carcinoma of lung and thymus, head and neck, and reported the recommended dose were 180 mg/m 2 of paclitaxel and 100 mg/m 2 of nedaplatin [13]. We considered that the results were reliable although the patients in these studies have not had prior pelvic radiation, so we initiated a phase II trial to evaluate the activity and toxicity of the combination of these two agents in 2007.…”
Section: Introductionmentioning
confidence: 96%